Deciphering the Signal From the Noise: Caregivers' Information Appraisal and Credibility Assessment of Cancer-Related Information Exchanged on Social Networking Sites. (20th April 2019) - Gage-Bouchard, Elizabeth A.; LaValley, Susan; Devonish, Julia A.
With the rise in the use of the Internet for health-related purposes, social networking sites (SNSs) have become a prominent platform for cancer communication and information exchange. Studies of cancer communication on SNS have mostly focused on understanding the quantity, content, quality, and user engagement (eg, likes and comments) with cancer-related information on SNS. There is less of an understanding of when and why people coping with cancer turn to SNS for cancer-related information, and how users appraise the credibility of cancer-related information obtained on SNS. In this study, we use data from in-depth qualitative interviews with 40 primary caregivers of pediatric patients with cancer to examine how cancer caregivers engage in information appraisal and credibility assessment of cancer-related information obtained on SNS. Findings show that cancer caregivers turned to SNS for cancer-related information because information on SNS was immediate, targeted in response to specific caregiver questions and concerns, and tailored to the specific information needs of cancer caregivers. Cancer caregivers evaluated the credibility of cancer-related information obtained on SNS through assessment of the SNS user who posted the information, frequency the same information was shared, and external corroboration. Findings have important implications for cancer communication and information interventions and point to elements of SNS cancer communication that can be integrated into health professional–facilitated communication and cancer information strategies.